Digital radiography detectors - A technical overview: Part 1 - Lança, Luís (2009)
During the last two decades screen-film (SF) systems have been replaced by digital X-ray systems. The advent of digital technologies brought a number of digital solutions based on different detector and readout technologies. Improvements in technology allowed the development of new digital technologies for projection radiography such as computed radiography (CR) and digital radiography (DR). The large number of scientific papers concerning digital X-ray systems that have been published over the last 25 years indicates the relevance of these technologies in healthcare. There are important differences among different detector technologies that may affect system performance and image quality for diagnostic purposes. Radiographers are expected to have an effective understanding of digital X-ray technologies and a high level of knowledge and awareness concerning the capabilities of these systems. Patient safety and reliable diagnostic information are intrinsically linked to these factors. In this review article - which is the first of two parts - a global overview of the digital radiography systems (both CR and DR) currently available for clinical practice is provided.